Extending the potential of Polydimethylsiloxane microchips - lbáñez, Alfredo (Pontificia Universidad Católica del Perú, 2005)
The search for microchannel wall modifications of simple use, that provide the desired functionality while the nonspecific adsorption is reduced to a mínimum, has allowed the development of new wall coatings. Specifically, the study of modifications that will enable to create robust microfluidic devices for the direct analysis of complex samples in which no sample pretreatment is required, are becoming a very important field of research, since they will allow microfluidic devices to become the analytical tool of choice for pharmaceutical and bioanalytical research fields.

La búsqueda de modificaciones a superficies de microcanales de fácil empleo, que provean la funcionalidad deseada y a la vez reduzcan la adsorción no específica, ha permitido el desarrollo de nuevos recubrimientos superficiales. Específicamente, el estudio de aquellas modificaciones que permitan la creación de dispositivos de microfluidos para el análisis directo de muestras complejas, donde no se necesite tratamientos preliminares, se están convirtiendo en un campo muy importante de investigación, puesto que el dispositivo de microfluidos constituirá una importante herramienta de selección para la investigación en estudios farmacéuticos y bioanalíticos.
Extending the potential of Polydimethylsiloxane microchips
Keywords: Química; https://purl.org/pe-repo/ocde/ford#1.04.00